Effects Of Addition Of Systemic Tramadol Or Adjunct Tramadol To Lidocaine Used For Intravenous Regional Anesthesia In Patients Undergoing Hand Surgery - مراد, رهام (Latakia University Journal -Medical Sciences Series, 2021)
Background and objective: Intravenous Regional Anesthesia (IVRA) is an easily applicated, cost effective technique and it is ideal method for short lasting procedures. Nevertheless, IVRA has some disadvantages including slow onset and short duration. To overcome these disadvantages some adjunct agents were added to local anesthetics (opioids, NSAIDs, clonidine, tramadol). The present study aimed to compare the effects of addition of systemic tramadol or adjunct tramadol to lidocaine to find which better in onset of the block, duration of sensory block, degree of pain, patients needed analgesics, analgesics consumption. Methods: 60 patients underwent hand surgery at Al -Mouasat University Hospital between 2019 and 2020 were studied . The patients were divided into 3 groups: group 1, patients who underwent IVRA with lidocaine(20patients), and group 2, those who underwent IVRA with lidocaine and systemic tramadol was added (20 patients), group 3, those who underwent IVRA with tramadol added to lidocaine (20patients) . The studied variables include: patients’ data ( Age, gender, weight, height, ASA), duration of surgery, duration of tourniquet, onset of sensory block, duration of sensory block, degree of pain (VAS score ) , number of patients who needed analgesics and analgesics consumption, These variables were compared between the three groups. Results: sensory block onset time was shorter in LD+TRA group than LD+sysTRA. Duration of analgesia was longer in LD+TRA group than LD+sysTRA. Patients who needed fentanyl as analgesic during operation were: 25% in (LD+TRA group) and 75% in (LD+sysTRA group). Fentanyl consumption was lower in (LD+TRA) Conclusion: administration of tramadol as adjunct showed some clinical benefits by providing a shorter onset time of sensory block, longer acting time of sensory block , decreasing pain and analgesic requirement so it was better than systemic tramadol.